2008
DOI: 10.1002/bit.22027
|View full text |Cite
|
Sign up to set email alerts
|

Transient gene delivery for functional enrichment of differentiating embryonic stem cells

Abstract: There is a critical need for new sources of hepatocytes, both clinically to provide support for patients with liver failure and in drug discovery for toxicity, metabolic and pharmacokinetic screening of new drug entities. We have reported previously a variety of methods for differentiating murine embryonic stem (ES) cells into hepatocyte-like cells. One major challenge of our work and others in the field has been the ability to selectively purify and enrich these cells from a heterogeneous population. Traditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…2,[6][7][8][9] Recently, we developed a transient gene delivery system to deliver two fluorescent liver-specific reporter plasmids into differentiating, semi-mature murine embryonic stem (ES) cells for enriching a subpopulation of hepatocyte-like cells. 10 The benefit of the transient expression of the plasmids fulfilled the system's needs, as the activation of the fluorescent reporters was only necessary up to and through the completion of the cell sorting. Nonetheless, the scale-up of this system is limited by inherent low plasmid transfection efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,[6][7][8][9] Recently, we developed a transient gene delivery system to deliver two fluorescent liver-specific reporter plasmids into differentiating, semi-mature murine embryonic stem (ES) cells for enriching a subpopulation of hepatocyte-like cells. 10 The benefit of the transient expression of the plasmids fulfilled the system's needs, as the activation of the fluorescent reporters was only necessary up to and through the completion of the cell sorting. Nonetheless, the scale-up of this system is limited by inherent low plasmid transfection efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In earlier work, we found that purifying differentiating ES cells expressing the Cyp7A1driven reporter yields greater hepato-specific functional enrichment than cells sorted with a more ubiquitous reporter driven by the albumin enhancer/promoter. 10 In the current study, we first assessed the role of serum starvation in modulating transfection efficiency using a general constitutive CMV-driven plasmid. We then specifically targeted liver-specific cells using the Cyp7A1 reporter in an effort to purify the number of cells in this subpopulation expressing the reporter.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] It is hypothesized that by controlling EB formation, it may be possible to control or enrich specified ES cell differentiation. [9][10][11] Previous studies have demonstrated selective differentiation of osteoblasts from ES cells via EB culture with factors including ascorbic acid, b-glycerophosphate (BGP), and the osteoinductive glucocorticoid dexamethasone (Dex). [12][13][14] In vitro cultured osteoblasts hold great promise for tissue repair and regeneration of bone, damaged as a result of disease and trauma.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Thus, several studies have used ESC lines transfected with the green fluorescent protein reporter gene controlled by hepatocytespecific promoters to select and/or detect ESC-derived hepatocytes. 9,10 However, this technique is relatively time consuming and leads to significant cell injury. Further, genetic modification carries risks such as possible tumor formation.…”
Section: Introductionmentioning
confidence: 99%